2023
DOI: 10.1186/s40249-023-01136-6
|View full text |Cite
|
Sign up to set email alerts
|

Tackling barriers to scale up human papillomavirus vaccination in China: progress and the way forward

Xue-Lian Zhao,
Shang-Ying Hu,
Jia-Wei Hu
et al.

Abstract: The human papillomavirus (HPV) vaccine is the first vaccine developed specifically targeting the prevention of cervical cancer. For more than 15 years, China has expedited a series of efforts on research and development of the domestically manufactured HPV vaccines, producing local population-based evidence, promoting free HPV vaccination from pilots, and launching action plans to tackle barriers in the scale-up of HPV vaccination. To further roll out the HPV vaccination program in China, several challenges sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Our results demonstrated that the co-testing of cervical HPV 33/35/52/53/56/58 with HPV 16/18 had better AUC values compared to the clinically well-recognized cervical HPV 16/18 detection. At present, five types of HPV vaccines have been approved: HPV-2 (16, 18) from three different manufacturers, HPV-4 (6, 11, 16, 18), and HPV-9 (6, 11, 16, 18, 31, 33, 45, 52, 58) [ 74 ]. Our results also highlighted the significance of HPV 35/53/56 in cervical lesions, although their association with high-grade lesions is not as clear as that of HPV 16/18/52/58.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that the co-testing of cervical HPV 33/35/52/53/56/58 with HPV 16/18 had better AUC values compared to the clinically well-recognized cervical HPV 16/18 detection. At present, five types of HPV vaccines have been approved: HPV-2 (16, 18) from three different manufacturers, HPV-4 (6, 11, 16, 18), and HPV-9 (6, 11, 16, 18, 31, 33, 45, 52, 58) [ 74 ]. Our results also highlighted the significance of HPV 35/53/56 in cervical lesions, although their association with high-grade lesions is not as clear as that of HPV 16/18/52/58.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study found that practical barriers to vaccination, particularly accessibility issues (e.g., insufficient supply and high price of vaccines), are the most prominent concern among the public, which align with a previous study. 31 In contrast with high-income countries, improving accessibility is the most paramount to enhancing HPV vaccination coverage in China, and the change in public attitude and social norms should be the first step of policy change. It is imperative for the Chinese government to prioritize addressing the barriers found in social media listening and survey studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Lance Rodewald highlights China’s swift mobilization of resources to achieve widespread COVID-19 vaccine coverage, advocating for the application of this infrastructure and experience to sustain high immunization rates as per IA2030 objectives, across all age groups for all WHO-recommended vaccines [ 7 ]. Prof. Fanghui Zhao and colleagues discuss the advances and challenges in China’s approach to HPV vaccination as a measure against cervical cancer, acknowledging significant progress but also calling attention to the need for stable vaccine supply, fair pricing, and a focus on marginalized populations to ensure equitable vaccine access [ 8 ]. A collaborative analysis by Prof. Shenglan Tang’s Duke Kunshan University team and Prof. Fuqiang Cui’s Peking University team examines the sluggish uptake of higher-valent paediatric combination vaccines in China, citing legislative and public awareness barriers while recommending a comprehensive promotion strategy that includes stricter vaccination law enforcement, schedule alignment, and enhanced vaccine research and development [ 9 ].…”
Section: Key Findingsmentioning
confidence: 99%